(untitled) (Indian Journal of Animal Production and Management, 2024)
A trial was conducted to assess the growth performance of Soviet Chinchilla rabbit under different feeding regimes at Livestock Farm Complex, Madhavaram Milk Colony, Chennai-51. Thirty Soviet Chinchilla weaned bunnies of both sexes aged around six weeks were randomly selected and divided into three groups namely T1 (Guinea grass + Concentrate), T2 (Hydroponic Maize + Concentrate) and T3 (Hydroponic Cowpea +Concentrate). All the groups were reared under similar intensive system of management. The dressing percentage of rabbits in T1, T2 and T3 were 59.40±0.87,60.20±1.50 and 61.20±0.97 respectively. There was no significant difference in dressing percentage between the treatment groups. The meat bone ratio in T3 was significantly higher than T1 and T2. The carcass characteristics did not differ between the treatment groups. It is concluded from this study the hydroponic fodder production technology can be recommended for broiler rabbit production in urban, peri-urban areas where land availability for fodder production is a constraint.